A cost-effective, open-source laboratory system for 3D photogrammetric analysis of corals - Alvaro Romo; Cristina Gutiérrez-Zárate; Meri Bilan; Andrea Gori; Alfredo Veiga; Rodrigo Pérez; Maria Rakka; António Godinho; Timm Schoening; Andrew Carey; Marina Carreiro-Silva; Covadonga Orejas (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

The hanging gardens of Blanes Canyon, Northwestern Mediterranean Sea - Meri Bilan; Jordi Grinyó; Cecilia Cabrera; Andrea Gori; Andreu Santín; Veerle A.I. Huvenne; Marie-Claire Fabri; Marta Arjona-Camas; Sarah Paradis; Claudio Lo Iacono; Stefano Ambroso; Ruth Durán; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Non-indigenous polychaetes along the Salento Peninsula: new records and first molecular data - JOACHIM LANGENECK; MATTEO PUTIGNANO; DESIRÈE DIMICHELE; ADRIANA GIANGRANDE; MERI BILAN; ANDREA TOSO; LUIGI MUSCO (Mediterranean Marine Science, 2024)
The Salento Peninsula represents the eastern-most edge of the Italian Peninsula, and one of the first areas to be invaded by thermophilic non-indigenous species. The diversity of non-indigenous polychaetes occurring along the Salento Peninsula is reviewed based on literature data and new samples. Overall, fifteen non-indigenous polychaetes were recorded; among them, Syllis similisunzima is reported for the first time in the Mediterranean Sea; Lepidonotus tenuisetosus is recorded for the first time in Italian waters; Pseudonereis anomala, until now known only for Sicily, is reported for the first time from the Italian Peninsula; Dorvillea similis is a first record for the Ionian and Adriatic Sea. 16S rDNA and COI sequences were obtained for eleven species, allowing us in some cases to confirm their identity and/or geographical origin, while in the case of some species they represent the first molecular data ever obtained.

First insights into the embryo and larval biology of the antipatharian coral Antipathella wollastoni - Maria Rakka; Antonio Godinho; Meri Bilan; Marina Carreiro-Silva (Marine Biology, 2024)

Vulnerability of six cold-water corals to sediment resuspension from bottom trawling fishing - Meri Bilan; Andrea Gori; Jordi Grinyó; Marina Biel-Cabanelas; Xènia Puigcerver-Segarra; Andreu Santín; Stefano Piraino; Sergio Rossi; Pere Puig (Marine Pollution Bulletin, 2023)

Natural hypoxic conditions do not affect the respiration rates of the cold-water coral Desmophyllum pertusum (Lophelia pertusa) living in the Angola margin (Southeastern Atlantic Ocean) - Andrea Gori; Covadonga Orejas; Furu Mienis; Christine Ferrier-Pagès; Meri Bilan; Sebastian Flöter; Stephanie Reynaud; Andrew K. Sweetman; J Murray Roberts; Claudia Wienberg; Dierk Hebbeln (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Extremely rapid withdrawal behaviour of the sea pen Protoptilum cf. carpenteri in the deep Mediterranean - Stefano Ambroso; Jordi Grinyó; Meri Bilan; Pere Puig (Marine Biodiversity, 2021)

Where Is More Important Than How in Coastal and Marine Ecosystems Restoration - Simonetta Fraschetti; Chris McOwen; Loredana Papa; Nadia Papadopoulou; Meri Bilan; Christoffer Boström; Pol Capdevila; Marina Carreiro-Silva; Laura Carugati; Emma Cebrian; Marta Coll; Thanos Dailianis; et al. (Frontiers in Marine Science, 2021)
Restoration is considered an effective strategy to accelerate the recovery of biological communities at local scale. However, the effects of restoration actions in the marine ecosystems are still unpredictable. We performed a global analysis of published literature to identify the factors increasing the probability of restoration success in coastal and marine systems. Our results confirm that the majority of active restoration initiatives are still concentrated in the northern hemisphere and that most of information gathered from restoration efforts derives from a relatively small subset of species. The analysis also indicates that many studies are still experimental in nature, covering small spatial and temporal scales. Despite the limits of assessing restoration effectiveness in absence of a standardized definition of success, the context (degree of human impact, ecosystem type, habitat) of where the restoration activity is undertaken is of greater relevance to a successful outcome than how (method) the restoration is carried out. Contrary to expectations, we found that restoration is not necessarily more successful closer to protected areas (PA) and in areas of moderate human impact. This result can be motivated by the limits in assessing the success of interventions and by the tendency of selecting areas in more obvious need of restoration, where the potential of actively restoring a degraded site is more evident. Restoration sites prioritization considering human uses and conservation status present in the region is of vital importance to obtain the intended outcomes and galvanize further actions.

Active Ecological Restoration of Cold-Water Corals: Techniques, Challenges, Costs and Future Directions - Maria Montseny; Cristina Linares; Marina Carreiro-Silva; Lea-Anne Henry; David Billett; Erik E. Cordes; Christopher J. Smith; Nadia Papadopoulou; Meri Bilan; Fanny Girard; Heidi L. Burdett; Ann Larsson; et al. (Frontiers in Marine Science, 2021)
Cold-water coral (CWC) habitats dwell on continental shelves, slopes, seamounts, and ridge systems around the world’s oceans from 50 to 4000 m depth, providing heterogeneous habitats which support a myriad of associated fauna. These highly diverse ecosystems are threatened by human stressors such as fishing activities, gas and oil exploitation, and climate change. Since their life-history traits such as long lifespan and slow growth rates make CWCs very vulnerable to potential threats, it is a foremost challenge to explore the viability of restoration actions to enhance and speed up their recovery. In contrast to terrestrial and shallow-water marine ecosystems, ecological restoration in deep marine environments has received minimal attention. This review, by means of a systematic literature search, aims to identify CWC restoration challenges, assess the most suitable techniques to restore them, and discuss future perspectives. Outcomes from the few restoration actions performed to date on CWCs, which have lasted between 1 to 4 years, provide evidence of the feasibility of coral transplantation and artificial reef deployments. Scientific efforts should focus on testing novel and creative restoration techniques, especially to scale up to the spatial and temporal scales of impacts. There is still a general lack of knowledge about the biological, ecological and habitat characteristics of CWC species exploration of which would aid the development of effective restoration measures. To ensure the long-term viability and success of any restoration action it is essential to include holistic and long-term monitoring programs, and to ideally combine active restoration with natural spontaneous regeneration (i.e., passive restoration) strategies such as the implementation of deep-sea marine protected areas (MPAs). We conclude that a combination of passive and active restoration approaches with involvement of local society would be the best optimal option to achieve and ensure CWC restoration success.

Habitat Features and Their Influence on the Restoration Potential of Marine Habitats in Europe - Trine Bekkby; Nadia Papadopoulou; Dario Fiorentino; Chris J. McOwen; Eli Rinde; Christoffer Boström; Marina Carreiro-Silva; Cristina Linares; Guri Sogn Andersen; Elizabeth Grace Tunka Bengil; Meri Bilan; Emma Cebrian; et al. (Frontiers in Marine Science, 2020)

First description of polyp bailout in cold-water octocorals under aquaria maintenance - Maria Rakka; Meri Bilan; Antonio Godinho; Juancho Movilla; Covadonga Orejas; Marina Carreiro-Silva (Coral Reefs, 2019)